Thermoresponsive gel embedding extracellular vesicles from adipose stromal cells improves the healing of colonic anastomoses following irradiation in rats - Hadrien Alric; Noëlle Mathieu; Anna Sebbagh; Guillaume Peré; Christelle Demarquay; André Cronemberger; Arthur Berger; Benjamin Marcel; Claire Wilhelm; Florence Gazeau; Antoine Mariani; Mehdi Karoui; et al. (Communications Biology)
Abstract Anastomotic leak occurrence is a severe complication after colorectal surgery. Considering the difficulty of treating these leaks and their impact on patient care, there is a strong need for an efficient prevention strategy. We evaluated a combination of extracellular vesicles (EVs) from rat adipose-derived stromal cells with a thermoresponsive gel, Pluronic® F127 (PF-127) to prevent anastomotic leaks. The pro-regenerative and immunomodulatory potencies of EVs are assessed in vitro. In vivo efficacy are assessed in rat with a colonic anastomosis model after irradiation. Endoscopic, anatomical and histological data show a consistent effect of EVs + gel on the healing of colonic anastomosis. These results are illustrated by a smaller anastomotic ulcer size, less fibrosis and less inflammatory infiltrations in the EVs + gel group. This multi-modal investigation is the first to point-out the translational potential of EVs combined with PF-127 for the healing of high-risk colorectal anastomosis.